1992
DOI: 10.1901/jaba.1992.25-193
|View full text |Cite
|
Sign up to set email alerts
|

Triadic Instruction of Chained Food Preparation Responses: Acquisition and Observational Learning

Abstract: This research examined whether constant time delay would be effective in teaching students with moderate mental retardation in triads to perform chained tasks and whether observational learning would occur. Three chained snack preparation tasks were identified, and each student was directly taught one task. The other 2 students observed the instruction. The instructed student told the observers to watch and to turn pages of a pictorial recipe book. The teacher provided frequent praise to the instructed student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…Nevertheless, the two studies discussed suggest that preschool children with disabilities can learn basic first aid skills and that social modeling procedures are effective in teaching these skills. Although only one of these studies incorporated observational learning, others have found observational learning to be effective in teaching chained tasks to students with disabilities (Griffen, Wolery & Schuster, 1992;Schoen & Sivil, 1989). Thus observational learning seems to be a promising strategy for teaching safety skills.…”
Section: Timko and Sainatomentioning
confidence: 99%
“…Nevertheless, the two studies discussed suggest that preschool children with disabilities can learn basic first aid skills and that social modeling procedures are effective in teaching these skills. Although only one of these studies incorporated observational learning, others have found observational learning to be effective in teaching chained tasks to students with disabilities (Griffen, Wolery & Schuster, 1992;Schoen & Sivil, 1989). Thus observational learning seems to be a promising strategy for teaching safety skills.…”
Section: Timko and Sainatomentioning
confidence: 99%
“…The University of Kentucky Checklist for Collaborative Field-Based Research is a result of experiences gained by the authors when implementing applied research in classrooms in which teachers implemented interventions (Collins, Branson, & Hall, 1995;Collins & Griffen, 1996;Collins, Schuster, & Nelson, 1992;Collins, Stinson, & Land, 1993;Doyle, Gast, Wolery, Ault, & Meyer, 1992;Doyle, Wolery, Ault, Gast, & Wiley, 1989;Griffen, Wolery, & Schuster, 1992;Hemmeter et al, 1996;Hemmeter, Towne, & Collins, in progress). These studies have involved (a) implementation of the research methods by direct-service providers currently teaching in the public schools, (b) direct supervision of the implementation by university staff, and (c) overall supervision of the investigations by faculty serving as co-principal investigators.…”
Section: Development Of the Checklistmentioning
confidence: 99%
“…Werts, Caldwell, and Wolery (1996), for example, found that students with disabilities acquired chained academic tasks such as using a calculator and playing an audiotape after systematically observing proficient peer models perform those tasks. Similarly, Griffen, Wolery, and Schuster (1992) showed that students with disabilities acquired almost all of the steps necessary to independently complete snack preparation tasks after observing other students receive direct instruction on the tasks. These results suggest that a useful strategy for establishing new skills is to arrange for the systematic observation of another individual modeling or receiving direct instruction on the skill.…”
mentioning
confidence: 94%